Calculating the Pace of Change During the COVID Era - Jill Channing (Academic Chairpersons Conference Proceedings, 2022)
The pandemic has caused ongoing economic, health, and educational challenges over the past two years. At the beginning of the pandemic, leaders were most concerned about immediate issues such as distance learning and safety for faculty, staff, and students. Now that institutions have returned to in-person learning, leaders must move forward with strategic planning and action with pandemic issues still playing significant roles in decision-making. During this session, participants will learn and discuss approaches for managing the pace of change and emotionally intelligent strategic planning during this challenging historical period.
Keywords: change leadership; pandemic leadership; strategic planning; crisis management; health and leadership